Janus particles: from concepts to environmentally friendly materials and sustainable applications - Marschelke, Claudia; Fery, Andreas; Synytska, Alla (Colloid and Polymer Science, 2020)
Janus particles represent a unique group of patchy particles combining two or more different physical or chemical functionalities at their opposite sides. Especially, individual Janus particles (JPs) with both chemical and geometrical anisotropy as well as their assembled layers provide considerable advantages over the conventional monofunctional particles or surfactant molecules offering (a) a high surface-to-volume ratio; (b) high interfacial activity; (c) target controlling and manipulation of their interfacial activity by external signals such as temperature, light, pH, or ionic strength and achieving switching between stable emulsions and macro-phase separation; (d) recovery and recycling; (e) controlling the mass transport across the interface between the two phases; and finally (f) tunable several functionalities in one particle allowing their use either as carrier materials for immobilized catalytically active substances or, alternatively, their site-selective attachment to substrates keeping another functionality active for further reactions. All these advantages of JPs make them exclusive materials for application in (bio-)catalysis and (bio-)sensing. Considering “green chemistry” aspects covering biogenic materials based on either natural or fully synthetic biocompatible and biodegradable polymers for the design of JPs may solve the problem of toxicity of some existing materials and open new paths for the development of more environmentally friendly and sustainable materials in the very near future. Considering the number of contributions published each year on the topic of Janus particles in general, the number of contributions regarding their environmentally friendly and sustainable applications is by far smaller. This certainly pinpoints an important challenge and is addressed in this review article. The first part of the review focuses on the synthesis of sustainable biogenic or biocompatible Janus particles, as well as strategies for their recovery, recycling, and reusability. The second part addresses recent advances in applications of biogenic/biocompatible and non-biocompatible JPs in environmental and biotechnological fields such as sensing of hazardous pollutants, water decontamination, and hydrogen production. Finally, we provide implications for the rational design of environmentally friendly and sustainable materials based on Janus particles. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-04-14
Keywords: Application; Biotechnology; Environment; Green chemistry; Janus particles; Recovery; Sustainability